2016
DOI: 10.3389/fpls.2016.01773
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Source and Rate Management Improve Maize Productivity of Smallholders under Semiarid Climates

Abstract: Nitrogen is one of the most important factor affecting maize (Zea mays L.) yield and income of smallholders under semiarid climates. Field experiments were conducted to investigate the impact of different N-fertilizer sources [urea, calcium ammonium nitrate (CAN), and ammonium sulfate (AS)] and rates (50, 100, 150, and 200 kg ha−1) on umber of rows ear−1 (NOR ear−1), number of seeds row−1 (NOS row−1), number of seeds ear−1 (NOS ear−1), number of ears per 100 plants (NOEP 100 plants−1), grain yield plant−1, sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…uptake efficiency and the utilization efficiency [ 4 6 ]. A number of physiological and environmental traits can affect the NUE in plants, including N source [ 7 , 8 ], N concentration and the remobilization of N from senescent tissues [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…uptake efficiency and the utilization efficiency [ 4 6 ]. A number of physiological and environmental traits can affect the NUE in plants, including N source [ 7 , 8 ], N concentration and the remobilization of N from senescent tissues [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2016) wrote a comprehensive review on the sustainable farming practices that could impede climate change through reducing carbon (C) footprints. In a study, direct and indirect N 2 O emission from cereal production was found to be 12 times higher in 2011 compared with 1970, while NUE decreased by approximately 74% in that period in Brazil (Amanullah et al, 2016). The authors attributed these results to increased consumption of N fertilizer and predicted that an increase in NUE by 2.4% from current figure would reduce use of N fertilizer worth US$21 million, resulting in reduced N 2 O emission (Amanullah et al, 2016).…”
Section: Improvement Of Nue For Mitigating Environmental Issuesmentioning
confidence: 99%
“…In a study, direct and indirect N 2 O emission from cereal production was found to be 12 times higher in 2011 compared with 1970, while NUE decreased by approximately 74% in that period in Brazil (Amanullah et al, 2016). The authors attributed these results to increased consumption of N fertilizer and predicted that an increase in NUE by 2.4% from current figure would reduce use of N fertilizer worth US$21 million, resulting in reduced N 2 O emission (Amanullah et al, 2016). A meta-analysis of 19 published studies indicated that N 2 O emission per unit of harvested product, called yield-scaled N 2 O emission, reduced 12.7–7.1 g N 2 O-N kg −1 N uptake with an increase of NUE from 19 to 75% (Sowers et al, 1994).…”
Section: Improvement Of Nue For Mitigating Environmental Issuesmentioning
confidence: 99%
“…On the other hand, the use of organic fertilizers (e.g., animal manure, crop residues and green manure) as alternative source of chemicals holds promise. Nitrogen is the most yield-limiting nutrient in crop production worldwide and mainly the most important factor needed for improving crop productivity and profitability (Guo et al, 2016 andAmanullah et al, 2016). Rotation is one of the valuable tools for nutrient recycling, which accelerate the microbial activity of the soil, permits better nutrient accessibility and higher crop yield (Pokhrel and Pokhrel 2013).…”
Section: Introductionmentioning
confidence: 99%